Peningkatan Literasi Matematika Siswa SMA Nurul Jadid melalui Program Bimbingan Belajar Interaktif - Arini Hidayati; Shofia Hidayah; Adis Adelia (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
This community service program aims to increase the mathematical literacy of Nurul Jadid High School students through an interactive tutoring program. Mathematical literacy is a student's ability to understand, analyze and solve mathematical problems in various contexts of daily life. Based on initial observations, it was found that many students had difficulty understanding basic mathematical concepts, so effective intervention was needed to improve their competence. The methods used in this program include the stages of identifying needs, preparing learning materials, implementing tutoring, and evaluating the success of the program. Tutoring is carried out interactively with a student-centered approach, where students are actively involved through discussions, group work and the use of digital learning media. In addition, intensive assistance is provided to help students overcome specific obstacles they face in learning mathematics. The program results show a significant increase in students' mathematical literacy skills, as measured through pre-test and post-test. Students are not only able to solve math problems better, but also show a deeper understanding of the concepts being taught. Apart from that, this program also increases students' learning motivation. In conclusion, this interactive tutoring program has proven to be effective in increasing the mathematical literacy of Nurul Jadid High School students. It is hoped that this program can become a model that can be replicated in other schools to help students develop better mathematics competencies